Local entrepreneurship through a multistakeholders' tourism living lab in the post‐violence/peripheral era in the Basque Country. Issue 3 (14th June 2018) - Calzada, Igor
Abstract: This paper examines a transformative tourism case study driven by local entrepreneurship in the coastal and post‐violence/peripheral village of Zumaia, in the Basque Country (Spain). This paper aims at addressing an innovative methodology called "Tourism Living Lab through Multistakeholders' Penta Helix framework" in response to a globalized trend of increasing visitors. The result shows democratic tourism policy‐making practices at the local level, including: (i) a participatory strategic formulation process; (ii) by fostering a local entrepreneurial ecosystem to overcome "tourism‐phobia"; (iii) while renewing local identity; and (iv) through bridging social capital for a new post‐violence era in the Basque Country. Resumen: Este artículo examina un estudio de caso de turismo transformador, impulsado por el espíritu empresarial local en la aldea costera y periférica/post‐violencia de Zumaia, en el País Vasco en España. El objetivo de este artículo es abordar una metodología innovadora llamada "laboratorio vivo de turismo mediante un marco pentahelicoidal de múltiples partes interesadas", en respuesta a una tendencia globalizada de aumento de los visitantes. El resultado muestra prácticas democráticas de formulación de políticas turísticas a nivel local, como: (i) un proceso participativo de formulación estratégica; (ii) mediante el fomento de un ecosistema emprendedor local para superar la "fobia al turismo"; (iii) renovando al mismo tiempo la identidad local; y (iv) mediante la creación de puentes entre el capital social para una nueva era post‐violencia en el País Vasco. 抄録: 本稿では、バスク地方 (スペイン)の地中海沿岸にある、かつて暴動があり辺境の村であったスマイア (Zumaia)の、現地のアントレプレナーシップに後押しされて変化を遂げる観光業のケーススタディを行う。観光訪問者数の増加というグローバルなトレンドに対応するため、Tourism Living Lab through Multistakeholders' Penta Helix frameworkというイノベーティブな手法に取り組むことを目的とする。結果から、地域レベルでの観光業の政策策定の民主的な方法には以下が含まれる。1)一般参加型の戦略策定のプロセスを、2)バスク地方の暴動後の新しい時代のために、社会資本の連携を通して、3)「観光業恐怖」を克服するたまの地域のアントレプレナー的エコシステムを育成することによって行い、4)その一方で、地域のアイデンティティを一新する。